Step
*
1
of Lemma
rng_mssum_when_swap
1. s : DSet
2. r : Rng
3. f : |s| ⟶ |r|
4. b : 𝔹
⊢ ∀a:|s| List. (Σ{r} x ∈ a. (when b. f[x]) = (when b. Σ{r} x ∈ a. f[x]) ∈ |r|)
BY
{ ((Backchain ``rng_lsum_when_swap``) THEN Auto) }
Latex:
Latex:
1.  s  :  DSet
2.  r  :  Rng
3.  f  :  |s|  {}\mrightarrow{}  |r|
4.  b  :  \mBbbB{}
\mvdash{}  \mforall{}a:|s|  List.  (\mSigma{}\{r\}  x  \mmember{}  a.  (when  b.  f[x])  =  (when  b.  \mSigma{}\{r\}  x  \mmember{}  a.  f[x]))
By
Latex:
((Backchain  ``rng\_lsum\_when\_swap``)  THEN  Auto)
Home
Index